Byzantine sources for the crusades, 1095-1204
1 online resource (ix, 232 pages)
Keywords: "The Christian, Greek-speaking Byzantine empire was placed rather uneasily between western Christendom and the Islamic world during the Crusade era. The texts translated here include selections from Anna Komnene's description of the passage of the First Crusade in 1096-8 but also the less well-known one by Zonaras and the contemporary letters of the archbishop of Ohrid. The accounts of the Second Crusade by John Kinnamos and Niketas Choniates are translated as well as a contemporary letter and two poems. There are first-hand reminiscences of visits to the Latin East and a number of speeches in which the policies of Emperors John II and Manuel I are explained and extolled. Choniates' recollections of the passage of the German emperor, Frederick I Barbarossa, in 1189-90 as part of the Third Crusade are translated, as well as a curious account of an incident that supposedly occurred when King Philip II Augustus was travelling back to France. The Fourth Crusade had the greatest impact. Originally intended as an expedition to Egypt, it diverted to the Byzantine capital of Constantinople to restore Emperor Isaac II to the throne. Choniates, an eye-witness to these events, recounted how good relations broke down when the Byzantines proved unable to pay the promised reward. On 12 April 1204, the crusaders captured Constantinople and sacked the city. Later, as a refugee in Nicaea, Choniates wrote a series a speeches looking back on the disaster and rallying the Byzantines to recover the city"--